Hubungan Gaya Kepemimpinan dan Intepersonal Skills Kepala Sekolah Terhadap Kualitas Kerja Guru di SDN 30 Panaikang Kecamatan Minasatene Kabupaten Pangkep - Amir, Muh Akbar; Syarifuddin, Syarifuddin; W, Muhammad Fahreza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The research aims to determine 1) the relationship between the principal's leadership style and the quality of teacher work at SDN 30 Panaikang, Minasatene District, Pangkep Regency. 2) the relationship between the principal's interpersonal skills and the quality of teacher work at SDN 30 Panaikang, Minasatene District, Pangkep Regency. 3) To determine the relationship between the principal's leadership style and interpersonal skills on the quality of teacher work at SDN 30 Panaikang, Minasatene District, Pangkep Regency. The type of research used is quantitative research. The research location is SDN 30 Panaikang, Minasatene District, Pangkep Regency. The population in this study were all teachers, where the sample consisted of 10 teachers. The data analysis techniques used are research instrument testing, analysis prerequisite testing, descriptive analysis and correlation analysis. The results of the research show that 1) there is a relationship between the principal's leadership style and the quality of teacher work at SDN 30 Panaikang, Minasatene District, Pangkep Regency based on a sig value of 0.014 0.05, 2) there is a relationship between the principal's interpersonal skills and the quality of teacher work at SDN 30 Panaikang, Minasatene District, Pangkep Regency based on a sig value of 0.015 0.05, 3) Leadership Skills and Interpersonal Style have "strong" relationship to the quality of teacher work at SDN 30 Panaikang, Minasatene District, Pangkep Regency in the range of 0.60-0.799.